Empowering Learners and Educators - Joseph D. Novak (Universidad de Granada, 2012)
The most important factor leading to empowerment of individuals is the ability and commitment to achieve high levels of meaningful learning. Meaningful learning requires integration of new concepts and propositions into the learnerʼs cognitive structure to achieve high levels of organized knowledge that can be represented as knowledge models. Concept mapping and new educational strategies can facilitate the process.